A service-oriented application creation process in ubiquitous environments: Travel assistant mobile application. Issue 3 (4th September 2017) - Taktak, Hajer; Moussa, Faouzi
Abstract : Purpose: Many features constitute an adaptive system such as user model, interface specification, business functionalities and service implementation. Context awareness is an important facet of service oriented application creation dealing with the gathering, use and representation of context information. Generally, user interfaces and services communities work separately on the adaptation process and do not converge. The aim of this work is to manage the system's functionalities and the user interface that delivers data to the relevant consumer early since the design phase until the code generation. Design/methodology/approach: The authors discuss how a unified method based on a model-driven architecture for adaptive user interface and pervasive service creation eases the work of designers and developers, limits incompatibility issues and supports dynamic generation of systems adapted to different contexts of use. Findings: The proposed approach is able to support a semi-automatic ubiquitous application generation with service, behavior, presentation and content adaptation. Originality/value: In this paper, the authors tackle context-awareness at two levels: system functionalities and user interface generation. The authors also tackle adaptation at the specification and implementation levels.